A Strategy for Site‐ and Chemoselective C−H Alkenylation through Osmaelectrooxidative Catalysis. (18th November 2021) - Choi, Isaac; Messinis, Antonis M.; Hou, Xiaoyan; Ackermann, Lutz
Abstract: Herein, we disclose osmaelectrocatalyzed C−H activations that set the stage for electrooxidative alkyne annulations by benzoic acids. The osmium electrocatalysis enables site‐ and chemoselective electrooxidative C−H activations with unique levels of selectivity. The isolation of unprecedented osmium(0) and osmium(II) intermediates, along with crystallographic characterization and analyses by spectrometric and spectroscopic in operando techniques delineate a synergistic osmium redox catalyst regime. Detailed mechanistic studies revealed a facile C−H cleavage, which allows for an ample substrate scope, providing provide robust and user‐friendly access to annulated heterocycles. Abstract : The first osmium‐catalyzed electrooxidative C−H annulation is disclosed. While improved selectivities are possible, unprecedented osmium intermediates are presented along with detailed kinetic studies, which revealed the working mode of osmaelectrocatalysis.